Relationship and Responsiveness of three Upper-Limb tests in Patients with Chronic Obstructive Pulmonary Disease - Janaudis-Ferreira, T.; Hill, Kylie; Goldstein, R.; Wadell, K.; Brooks, D. (BC Decker Incorporated, 2013)
Purpose: To determine (1) the relationship among three common upper-limb tests for patients with chronic obstructive pulmonary disease (COPD): unsupported upper limb exercise test (UULEX), 6-minute pegboard and ring test (6PBRT), and a muscle-strength test using a hand-held dynamometer; and (2) the responsiveness of these three tests to changes after pulmonary rehabilitation that included a resistance arm-training programme.Methods: The study was a secondary analysis of a randomized controlled trial (RCT). The UULEX and the 6PBRT were used to measure peak arm exercise capacity and arm function, respectively. A handheld dynamometer was used to measure elbow and shoulder flexion force. We analyzed baseline data for all participants in the RCT, as well as baseline and post-PR data for those who completed 6-week follow-up testing.36 patients with COPD (mean forced expiratory volume in 1 second [FEV1] = 35% [SD 15%] predicted; age 66 [9] y) participated, of whom 13 completed an arm-training programme. The correlations among the test results ranged from 0.41 to 0.81 (p < 0.0001). Standardized response means were 1.0 for muscle force of elbow flexion, 1.2 for shoulder flexion, and 1.8 for the 6PBRT and UULEX.Conclusions: Although the three tests (UULEX, 6PBRT, and muscle-strength test using a hand-held dynamometer) are intended to measure different constructs, they were moderately to highly correlated with one another. The 6PBRT, UULEX, and muscle-strength test were demonstrated to be responsive to the resistance arm-training programme.